Flatwise compression behavior of 3D woven honeycomb composites. (18th September 2022) - Tripathi, Lekhani; Behera, Bijoya Kumar
Honeycomb being a cellular solid is a well-known core in sandwich structure and is considered an ideal structural material because of its high strength and shear stiffness, high impact strength, lower weight, excellent energy absorbing property, high crushing stress, and almost constant crushing force. In this study, 3D woven honeycomb structures were developed with different cell geometry by varying the cell size, free wall length, bonded wall length, opening angle, and the number of honeycomb layers keeping overall composite thickness and cell shape constant. The variation of cell geometry was carried out by changing the number of picks in the honeycomb wall. Composite samples were prepared from the honeycomb preforms with epoxy resin (matrix) using VARIM (vacuum-assisted resin infusion method) process and characterized for their flatwise compression behavior. It was found that the structural parameters influenced compression energy absorption. The results revealed that regular cell shape, smaller cell size, and higher number of layers of honeycomb composites exhibited higher specific energy absorption. These findings are useful in engineering design development and applications of 3D honeycomb composites.